Calibration and Validation of SWAT Model for Low Lying Watersheds: A Case Study on the Kliene Nete Watershed, Belgium - Shrestha, Narayan K.; Shakti, P C; Gurung, Pabitra (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Use of easily accessible; public domain modeling software called Soil and Water Assessment Tool (SWAT) and its testing in watersheds has become essential to check developers' claims of its applicability. The SWAT model performance on Kliene Nete Watershed (Belgium) is examined. Given the watershed’s characteristic of a low lying; shallow ground water table, the test becomes an interesting task to perform. This paper presents calibration and validation of the watershed covering area of 581km2 . Flow separation is carried on using Water Engineering Time Series Processing tool (WETSPRO) and shows that around 60% of the total fow is contributed by base fow. Altogether seven SWAT model parameters have been calibrated with heuristic approach for the time frame of 1994-1998. Validation of these calibrated parameters in another independent time frame (1999-2002) is carried out. The parameter CH_k2 (Channel Effective Hydraulic Conductivity) is found to be the most sensitive. Nash Sutcliff Efficiency (NSE) values for the calibration and validation periods are found to be 74 and 67 percent-age, respectively. These ‘goodness-of-ft’ statistics, supported by graphical representations, show that the SWAT model can simulate such watershed with reasonable accuracy. Key words: SWAT; WETSPRO; Kliene Nete Watershed (Belgium); NSE DOI: 10.3126/hn.v6i0.4194 Hydro Nepal Journal of Water, Energy and Environment Vol. 6, January 2010 Page: 47-51 Uploaded Date: 24 January, 2011